ANALISA TINGKAT PENGETAHUAN DAN PERILAKU TERHADAP PENGGUNAAN OBAT INFLUENZA DAN BATUK SECARA SWAMEDIKASI DI DESA MUARA BURNAI I KABUPATEN OGAN KOMERING ILIR - Mashuri Yusuf; Subur Widodo; Aqbar Raka Irwansyah (Fakultas MIPA Universitas Tulang Bawang Lampung, 2020)
Abtract Many Indonesian people do self-medication as an attempt to treat complaints / pain they experience, the benefit of self-medication is safe when used according to the rules, effective for eliminating complaints, cost efficiency, can play a role in making therapeutic decisions, self-medication is usually done to overcome complaints and minor illnesses that are often experienced by people, such as fever, pain, dizziness, cough, influenza, ulcers, intestinal worms, diarrhea, skin diseases and others. This study aims to determine the level of knowledge and behavior towards the use of influenza drugs and cough by self-medication in Muara Burnai I Village, Ogan Komering Ilir district. The research analyzed was descriptive observational. The sampling technique uses the accindental sampling method. The instrument used in this study was a questionnaire. The results of the analysis of the level of knowledge and behavior analysis showed that there was a relationship between the level of knowledge and the behavior of influenza drug use and cough by self-medication was analyzed using the Chi-Square test sample of 100 respondents. The results of this study indicate that 36% have high knowledge and 64% have low knowledge in self-influencing and cough swamedication while 43% have high behavior and 57% have low behavior in influenza and cough swamedication in Muara Burnai I Village, Ogan Komering Ilir District. Based on the Chi-Square test results showed that the value of p = 0,000 (0.05). Shows that there is a relationship between the level of knowledge and swamedication behavior in Muara Burnai I Village, Ogan Komering Ilir district. Keywords : Influenza and cough, drug use behavior, swamedication, knowledge level.